Factors controlling the chemical composition of colloidal and dissolved fractions in soil solutions and the mobility of trace elements in soils. (15th September 2016) - Gangloff, Sophie; Stille, Peter; Schmitt, Anne-Désirée; Chabaux, François
Abstract: The objectives of this study were to determine the processes and physico-chemical conditions that affect the composition of the soil solutions of a forest soil and to elucidate their impact on the transport of major and trace elements through the colloidal (0.2 μm to 5 kDa) and dissolved (<5 kDa) fractions in the first meter of soil. All experiments were performed with soil solutions obtained using lysimeter plates situated on an experimental spruce parcel of the Strengbach catchment (Northeastern France). The surface samples filtered at 0.2 μm facilitated the examination of the influence of litter decomposition on the chemical composition of the upper soil solutions. The impact of the soils biogeochemical conditions (pH, moisture, temperature, oxic or anoxic conditions) on litter decomposition was also examined. More particularly, the increase in NH4 + and NO2 − compounds in some of the soil solutions points to denitrification processes in an anoxic environment. Thus, under anoxic conditions, the soil solution is enriched in Ca, P, Mn and Zn, whereas under oxic conditions it is enriched in Al and Fe. The physico-chemical conditions are more seasonally dependent in the upper soil horizons than in the deeper ones and have an impact on the variability of the chemical composition of the soil solutions. The colloidal and dissolved fractions of the soil solutions were obtained by tangential flow ultra-filtration. The experimental results reveal that nutrients, such as NO3 − and P, are primarily in the dissolved fraction and consequently bioavailable; secondary minerals may be dissolved and/or precipitate in the colloidal fraction, such as pyromorphite (Pb5 (PO4 )3 (OH, Cl, F)). The results further indicate that microbial activity influences the composition of the colloidal and dissolved fractions, and possibly enriches the colloidal fraction in Ca, Mn and P, diminishes the concentrations of Pb, V, Cr and Fe in the dissolved fraction, and changes the structure of organic carbon (OC). These results are important for a better understanding of the role of the colloidal and dissolved (<5 kDa) fractions in the transport of the major and trace elements in soil solutions and, more particularly, the mobility of pollutants and the bioavailability of nutrients for forested ecosystems.